Analisis Tingkat Literasi Keuangan Syariah UMKM di Tasikmalaya - Zahra, Qiny Shonia Az; Nurhasanah, Elis (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Islamic financial inclusion and literacy has a fairly high gap with financial inclusion and literacy in general. Likewise with MSMEs, which are one of the driving wheels of the economy, the level of Islamic financial literacy is not yet known, especially for MSMEs in Tasikmalaya. The purpose of this study was to determine the level of Islamic financial literacy in food and beverage SMEs in Tasikmalaya. The research method uses the mix method, questionnaires using the guttman scale. The results showed that the level of MSME Islamic financial literacy in Tasikmalaya was in the low category, namely 41.6 percent. or are in the low category. Therefore socialization and promotion related to Islamic financial literacy are needed by MSMEs to increase knowledge and increase the level of MSME Islamic financial literacy in Tasikmalaya.